EFFECT OF DEVELOPMENT OF MARINE ECOTOURISM ON THE SOCIAL AND ECONOMIC LIFE AROUND THE COASTAL CAROLINA BEACH IN SOUTH BUNGUS VILLAGE BUNGUS TELUK KABUNG DISTRICT PADANG CITY WEST SUMATRA PROVINCE - Rahmat '; Lamun Bathara; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted on October 2014 in South Bungus Village BungusTeluk Kabung District Padang City West Sumatra Province. The purpose of thisresearch was to (1) Know the general picture maritime tourist attraction CoastalCarolina, (2) Determine the influence of the development of marine ecotourismCarolina against the social circumstances surrounding coastal communities, (3)Determine the influence of the development of marine ecotourism Carolina against theeconomic situation of coastal communities around . The method used in this study is asurvey method with descriptive data analysis.The results showed that the attraction Coastal Carolina has a beautiful naturalscenery with white sand and a variety of coral reefs and charming ornamental fish andseafood culinary tours that can be enjoyed by tourists. Influence the development ofmarine ecotourism Carolina against social circumstances surrounding coastalcommunities that social conflict societies, marriage with tourists, social ills, changes ineducation and health. Influence the development of marine ecotourism Carolina tocoastal communities around the state of the economy, namely the increased revenue inthe field of non-fishery, while the negative impact of nautical tourism on the economyCoastal Carolina is a decrease in revenue fishery.Keywords: Marine Ecotourism, Social and Economic Community Around, CoastalCarolina1) Mahasiswa Fakultas Perikanan dan Ilmu Kelautan, Universitas Riau